1970
DOI: 10.3329/bjar.v36i3.9264
|View full text |Cite
|
Sign up to set email alerts
|

Growth And Yield Components Of Wheat Under Water Stress Of Different Growth Stages

Abstract: A field experiment was conducted to determine the sensitivity of wheat to water stress and changes in water relations and yield of wheat (Triticum aestivum L.) under water stress conditions applied at different growth stages. The experiment comprised of two wheat cultivars and four water stress treatments, maintained by withholding water at tillering, anthesis, and at both stages. Water stress caused reduction in leaf relative water contents, water potential, osmotic potential, turgor potential, growth and yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
53
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 10 publications
13
53
0
1
Order By: Relevance
“…I 1 had significantly higher 1000-grain weight than all other water stress treatments in both seasons. Similar effects of water stress on 1000-grain weight were also reported by Qadir et al (1999), Dencic et al (2000) and Akram (2011). Furthermore, the highest mean values of 1000-kernel weight (51.72 and 50.95 g) in the first and second seasons, respectively, were obtained when nitrogen fertilizer was divided into four equal doses.…”
Section: -Kernel Weight (G)supporting
confidence: 71%
“…I 1 had significantly higher 1000-grain weight than all other water stress treatments in both seasons. Similar effects of water stress on 1000-grain weight were also reported by Qadir et al (1999), Dencic et al (2000) and Akram (2011). Furthermore, the highest mean values of 1000-kernel weight (51.72 and 50.95 g) in the first and second seasons, respectively, were obtained when nitrogen fertilizer was divided into four equal doses.…”
Section: -Kernel Weight (G)supporting
confidence: 71%
“…Many studies are in line with the findings of the present study that drought at tillering stage (Hussain et al 1987), during vegetative growth (Qadir et al 1999) and at crown root plus booting stage (Qamar et al 2011) caused reduction in LAI significantly in wheat than other irrigation treatments. Akram (2011), moisture stress at different crop growth stages affected CGR differently. …”
Section: Growth Indicesmentioning
confidence: 99%
“…Plant water status was affected under drought condition. Thus, plants grown under water deficit have low leaf Ψ w and turgor potential (Ψ p ) [7]. Therefore, the maintenance of appropriate plant water status during water deficit is essential for continued growth and this process can be achieved by stomatal regulation [8].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple characteristics of vascular structure have been investigated, such as modifications of the vascular bundle number and area and alteration of xylem/ phloem ratio, which are thought to be involved in the resistance of the plant to environmental stresses [18]. Several studies have shown that xylem and/or phloem vessel diameter was reduced in Ctenanthe setosa and Triticum aestivum plants subjected to drought stress [2][3][4][5][6][7][8][9][10][11][12][13][14]. Thus, xylem with narrow vessels is physiologically better protected against cavitation [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation